2015
DOI: 10.1093/jme/tjv037
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence Rates ofBorrelia burgdorferi(Spirochaetales: Spirochaetaceae),Anaplasma phagocytophilum(Rickettsiales: Anaplasmataceae), andBabesia microti(Piroplasmida: Babesiidae) in Host-SeekingIxodes scapularis(Acari: Ixodidae) from Pennsylvania

Abstract: The etiological agents responsible for Lyme disease (Borrelia burgdorferi), human granulocytic anaplasmosis (Anaplasma phagocytophilum), and babesiosis (Babesia microti) are primarily transmitted by the blacklegged tick, Ixodes scapularis Say. Despite Pennsylvania having in recent years reported the highest number of Lyme disease cases in the United States, relatively little is known regarding the geographic distribution of the vector and its pathogens in the state. Previous attempts at climate-based predictiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 43 publications
7
47
1
Order By: Relevance
“…We saw no evidence that coinfection occurred more or less often than expected based upon the co-infections predicted by combinations of the pathogens independent frequencies. Our coinfection rates for B. burgdorferi + A. phagocytophilum and B. microti+ A. phagocytophilum were similar to a prior study conducted in southwestern Pennsylvania [18]. In spite of these three pathogens potentially sharing some common animal reservoirs, we found B. burgdorferi to have an uneven distribution (independent of sample size) among the nine recreational areas we sampled which could be due to differences in prevalence of hosts these ticks feed on during the larvael or nymphal stages of their development [10].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…We saw no evidence that coinfection occurred more or less often than expected based upon the co-infections predicted by combinations of the pathogens independent frequencies. Our coinfection rates for B. burgdorferi + A. phagocytophilum and B. microti+ A. phagocytophilum were similar to a prior study conducted in southwestern Pennsylvania [18]. In spite of these three pathogens potentially sharing some common animal reservoirs, we found B. burgdorferi to have an uneven distribution (independent of sample size) among the nine recreational areas we sampled which could be due to differences in prevalence of hosts these ticks feed on during the larvael or nymphal stages of their development [10].…”
Section: Discussionsupporting
confidence: 84%
“…Additionally, the number and/or source of blood meals, and thus the opportunity for infection, could possibly be the reason for marginal differences in B. burgdorferi (p = 0.054) and A. phagocytophilum (p = 0.078) prevalence between male and female ticks [10]. The 27% prevalence rate for B. microti in this study could be attributed to regional variation [20] and sampling of I. scapularis ticks for microbial pathogens in a high incidence southwestern Pennsylvania county compared to prior studies which sampled ticks from random locations in western Pennsylvania [18,19,21]. In support of our findings, a study by Piesman, et al [22] demonstrated the wide prevalence of B. microti (2%-47%) in adult I. scapularis from four areas in eastern Massachusetts.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…No I. scapularis were collected during a statewide survey from 1963 to 1967 (Snetsinger 1968), whereas the tick was recorded from 49 of 67 counties by the late 1990s (Dennis et al 1998). A statewide survey conducted during 2012–2014 (Hutchinson et al 2015) revealed that the tick now is established in all 67 counties. It is likely that the east-to-west tick expansion across Pennsylvania continued into neighboring Ohio to the west, where active tick surveillance was conducted from 1983 to 2012.…”
Section: Discussionmentioning
confidence: 99%